Penerapan Metode Activity Relationship Chart (ARC) dan Total Closeness Rating (TCR) untuk Evaluasi Tata Letak Fasilitas di PT Lembur Hejo - Sinurat, Elysabeth July Aini; Hamdan, Aldo Abiyyu Dzaki; Rabbani, Miqdad Hafidz; Anjani, Ajeng; Rafli, Muhamad; Husyairi, Khoirul Aziz (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Facility layout efficiency is pivotal for the operational performance of PT Lembur Hejo’s hydroponic agribusiness. This study evaluates the effectiveness of the existing layout to identify workflow inefficiencies using a descriptive quantitative approach. Utilizing the Activity Relationship Chart (ARC) and Total Closeness Rating (TCR), functional relationships were mapped and prioritized. The results stratified facilities into three clusters: core production (TCR 176) as the highest priority, followed by employee support (TCR 80), and administrative facilities. While the analysis validated the efficiency of the production zone, it revealed a significant spatial dissonance regarding support facilities (office, dormitory, restrooms), which are currently misaligned with their functional priorities. Conclusively, this study demonstrates the efficacy of ARC/TCR in detecting latent inefficiencies beyond the core production area.